eLingua : Issue 2 : December 2017 / Academy of Language Studies - Mohd Yusof, Noor Laili; Aboo Bakar, Rofiza; Mohd Amin, Noraziah; Terng, Hoe Foo; Ab. Rahim, Suzana; Tazijan, Farina Nozakiah; Ismail, Rushita; Muhamad, Sabariah; Desa, Melati; Raja Berahim, Raja Rosila; Giap, Lim Soo (Academy of Language Studies, 2017)
1. ‘MAJLIS KEMUNCAK SAMBUTAN INOVASI PERINGKAT UiTM CAWANGAN PULAU PINANG (UiTMCPP) 2017’ 2. International Conference on Hajj, Umrah and Ziarah (ICHUZ 2017) 3. ICoFA 2017 4. Industrial Work Life and Internet of Things Talks by INTEL, Penang 5. International Conference and Competition on Teaching and Learning (I-Telearn) 2017 6. My_CASELT and LIID 2017 7. I-YES 2017 8. Seminar on Industrial Revolution 4.0 9. A report on the Toastmasters Presentation Skills (FYP 2) Program 2017 10. 2nd International Conference on Theory and Practice of Chinese Language Teaching 2017 11. 29th Southeast Asian (SEA) Games 2017 12. English Language Speaking Day 13. ELD Bertam 2017 14. MOU Signing between UiTM and Universitas Tanjungpura, Indonesia (23rd August 2017; Ballroom, Hotel UiTM Pulau Pinang) 15. A Joyful Language Day Indeed for Giatmara Trainees 16. KURSUS ASAS BAHASA JEPUN & BAHASA JERMAN 17. Mempelajari Simpulan Bahasa Mandarin: Yīmáobùbá 18. Juri Naik Lori 19. Best Ooo Masuk TV! 20. Terapi Air: Terapi Spatial dan Risiko bagi Pelatih Autistik